Alpha1-antitrypsin protects the immature mouse brain following hypoxic-ischemic injury - Zhang, Shan; Li, Wendong; Xu, Yiran; Li, Tao; Ek, Joakim; Zhang, Xiaoli; Wang, Yafeng; Song, Juan; Zhu, Changlian; Wang, Xiaoyang (Frontiers in Cellular Neuroscience, 2023)
Preterm brain injury often leads to lifelong disabilities affecting both cognitive and motor functions, and effective therapies are limited. Alpha1-antitrypsin (AAT), an endogenous inhibitor of serine proteinases with anti-inflammatory, anti-apoptotic, and cytoprotective properties, might be beneficial in treating preterm brain injury. The aim of this study was to investigate whether AAT has neuroprotective effects in a mouse preterm brain injury model. Preterm brain injury was induced on postnatal day 5, and mouse pups’ right common carotid arteries were cut between two ligations followed by hypoxia induction. Brain injury was evaluated through immunohistochemistry staining and magnetic resonance imaging. Fluoro-Jade B and immunohistochemistry staining were performed to investigate the neuronal cell death and blood-brain barrier (BBB) permeability. The motor function and anxiety-like behaviors were revealed by CatWalk gait analysis and the open field test. After hypoxia-ischemia (HI) insult, brain injury was alleviated by AAT treatment, and this was accompanied by reduced BBB permeability, reduced neuronal cell death and caspase-3 activation, and inhibition of microglia activation. In addition, AAT administration significantly improved HI-induced motor function deficiencies in mice. The neuroprotective effect of AAT was more pronounced in male mice. In conclusion, AAT treatment is neuroprotective against preterm brain injury in neonatal mice, and the effect is more pronounced in males.